2004
DOI: 10.1001/archotol.130.5.547
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cochlear Implants on Young Deaf Children

Abstract: uch evidence suggests that, early in life, auditory input and communication are essential for the normal development of language, cognition, and behavior. Thus, deaf children, who experience significant disruptions in auditory input, are likely to show delays not only in the production of oral language but in other important aspects of development such as visual attention and behavioral control. Cochlear implants have shown tremendous promise in restoring auditory information to deaf children and concomitant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 78 publications
5
32
0
3
Order By: Relevance
“…In fact, this result is aligned with studies about parental participation in the (re)habilitation of implanted children (Quittner et al 2004, Li et al 2004. The existing relation between the performance of the children in the hearing and language categories and the familial permeability in the therapeutic process reaffirms the importance of the family adequacy as eligibility criteria for the cochlear implant candidacy, especially in regards of the treatment motivation and of the children use of the device.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In fact, this result is aligned with studies about parental participation in the (re)habilitation of implanted children (Quittner et al 2004, Li et al 2004. The existing relation between the performance of the children in the hearing and language categories and the familial permeability in the therapeutic process reaffirms the importance of the family adequacy as eligibility criteria for the cochlear implant candidacy, especially in regards of the treatment motivation and of the children use of the device.…”
Section: Discussionsupporting
confidence: 64%
“…Psarros et al (2002) also found improvement of the consonant scores with the ACE strategy, and considered that the improvement of the speech perception obtained with the conversion of the Spectral Peak (SPEAK) strategy to the ACE strategy was significant, and that this improvement was more significant under noise, suggesting that the conversion of the SPEAK strategy to the ACE strategy is beneficial for children, and the ACE strategy may be an initial choice for them. Quittner et al (2004) emphasized that few studies investigate the effects of the cochlear implant on the multiple skills of the child, such as cognition and behavior. They highlighted that as far as the implant provides hearing access to the speech sounds and the child begins to respond to them, her ability to control her attention and behavior increases considerably, leveraging the interaction parents-child thus enriching the communication experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Research comparing the play of typically developing children and those with speech and language impairment has documented some consistent differences. Quittner, Leibach, and Marciel (2004) noted that children with hearing loss performed more poorly than age-matched hearing peers on measures of symbolic play. Children with disabilities have been observed to exhibit the same developmental play sequences as typical children but with differences in terms of both the quantity and quality of play.…”
Section: Using Play To Target Social Skillsmentioning
confidence: 99%
“…, Quittner et al (2004) or Schorr, (2005 the deprivation of auditory information and communication at an early age may be an obstacle for learning the main behavioral skills. In this sense, SLH specialist and classroom-teacher assessments did not reflect a clear existence of behavioral problems in implanted children.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the possible consequences derived from communication difficulties of children with cochlear implants and the possible effects on their development (Calderón & Greenberg, 2003;Quittner, Leibach, & Marciel, 2004;Stevenson, Kreppner, Pimperton et al, 2009), has led these authors to suggest that there are more behavioral problems in implanted students than in their hearing classmates (Anmyr, Larsson, Olsson, and Freijd, 2012;Worsfold & Kennedy, 2015;Vostanis, Hayes, Du Feu, & Warren, 1997).…”
Section: Introductionmentioning
confidence: 99%